2001
DOI: 10.1159/000045974
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in Maintenance Dialysis Patients

Abstract: In this investigation, we tried to find the incidence and characteristics of tuberculosis (TB) in dialysis patients previously found only in a small number of cases. We collected the cases of newly diagnosed TB patients in Taiwan during 1997. Simultaneously, all dialysis patients were collected and matched with the TB cases to identify the dialysis patients who had also contracted TB. The annual incidence of the dialysis population was 493.4/100,000, 6.9 times that of the general population (71.1/100,000). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 9 publications
(24 reference statements)
4
89
2
1
Order By: Relevance
“…Pien et al (23) (2). Admission-related complications are other factors associated mortality (3). The present study observed the development of CHF, nosocominal pneumonia, and gastrointestinal bleeding as complications which are not directly related to TB, during admission highly influenced the outcome.…”
Section: F I G U R E 1 T H E 2 4 -We E K S U R V I V a L U S I N G mentioning
confidence: 57%
See 2 more Smart Citations
“…Pien et al (23) (2). Admission-related complications are other factors associated mortality (3). The present study observed the development of CHF, nosocominal pneumonia, and gastrointestinal bleeding as complications which are not directly related to TB, during admission highly influenced the outcome.…”
Section: F I G U R E 1 T H E 2 4 -We E K S U R V I V a L U S I N G mentioning
confidence: 57%
“…The details of the 10 cases examined by QFT-2G are listed in Table 5 Previous studies reported a high frequency of cases of TB discovered in the first year of dialysis (3,4,13,19 HD (HD >1 year) T a b l e 3 . Ra d i o l o g i c a l Cl a s s i f i c a t i o n o f 1 6 P a t i e n t s wi t h P u l mo n a r y T u b e r c u l o s i s …”
Section: Qft-2gmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2006, Taiwan reported the highest rates of incident and prevalent ESRD requiring hemodialysis in the world at 418 and 2226 per million population, respectively (3). The annual incidence of TB in the Taiwanese dialysis population was 493.4 per 100,000 in 1997, which was 6.9 times higher than that of the general population (71.1 per 100,000) (4). Overall 1-year mortality in dialysis patients with TB was higher than in the general TB population (27.3% versus 13.0%, P Ͻ 0.05), but deaths attributable directly to TB were not different (1.7% versus 1.9%, P Ͼ 0.05) (4).…”
mentioning
confidence: 82%
“…Decades later, another study showed a signifi cantly increased risk of TB in patients with chronic renal failure who were undergoing dialysis 18 . In cohort studies, the relative risk of TB among such patients was 3.4 to 25.3 times greater than that among the general population [19][20][21][22] .…”
Section: Methodsmentioning
confidence: 99%